2001
DOI: 10.1007/s002590100489
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis and changes in glucose transport early after treatment of Morris hepatoma with gemcitabine

Abstract: Apoptosis has been described as an energy-consuming process. This combined in vivo/in vitro study investigated the effects of the antineoplastic agent gemcitabine on tumour metabolism and on the induction of apoptosis. Dynamic positron emission tomography (PET) measurements of fluorine-18 fluorodeoxyglucose (FDG) uptake were done in rats bearing Morris hepatoma prior to and after therapy with 90 mg gemcitabine/kg b.w. Furthermore, thymidine (TdR) incorporation into the DNA of these tumours was determined. In v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 17 publications
0
22
0
Order By: Relevance
“…89 However, because apoptosis must use energy, at least initially, glucose demand may increase temporarily in some clinical situations. 90 One example appears to be the "metabolic flare" often observed on 18 F-FDG PET images after hormonal therapy administrated for estrogen receptor-positive human breast cancer. 91 The metabolic flare is this select patient population may also be a useful indicator of responsiveness to anti-estrogen therapy as opposed to non-hormonal chemotherapy.…”
Section: © 2 0 0 8 L a N D E S B I O S C I E N C E D O N O T D I S mentioning
confidence: 99%
“…89 However, because apoptosis must use energy, at least initially, glucose demand may increase temporarily in some clinical situations. 90 One example appears to be the "metabolic flare" often observed on 18 F-FDG PET images after hormonal therapy administrated for estrogen receptor-positive human breast cancer. 91 The metabolic flare is this select patient population may also be a useful indicator of responsiveness to anti-estrogen therapy as opposed to non-hormonal chemotherapy.…”
Section: © 2 0 0 8 L a N D E S B I O S C I E N C E D O N O T D I S mentioning
confidence: 99%
“…In several pre-clinical studies gemcitabine demonstrated strong antitumor effects on HCC (29)(30)(31). Therefore, based on pre-clinical rationale gemcitabine was evaluated in patients with advanced HCC.…”
Section: Gemcitabinementioning
confidence: 99%
“…Another possible hypothesis is apoptotic reaction in denervated skeletal muscles. Apoptosis has been considered as an energy-consuming process that can be accompanied by an 18 F-FDG uptake increase (10). There were several previous studies that have demonstrated that muscle denervation stimulates mitochondrially mediated apoptosis (11).…”
Section: Discussionmentioning
confidence: 99%